Analisis Motivasi Siswa dalam Belajar Tatap Muka (Penelitian Pada Siswa Kelas IV SD Negeri 4 Cibunigelis) - Windy Marliana; Dedi Heryadi; Fajar Nugraha (Universitas Palan, 2023)
The purpose of this study was to describe students' learning motivation during face-to-face meetings and to find out the factors that influence the learning styles of students in class IV SDN Cibunigelis. The research method uses a descriptive method with a qualitative approach. Data collection techniques using observation, interviews, and documentation. Data were analyzed by using reduction, display, and conclusion. Sources of research data include: students and educators. The results showed that the learning motivation of students in face-to-face with characteristics tends to be more able to understand learning by observing the teacher when delivering material, as well as being more enthusiastic and diligent in carrying out assignments, influenced by students who have enthusiasm and good learning readiness. the 3 students had different motivations given by educators, RA students were generally able to observe educators when delivering lessons well, RA were better able to read and write quite well. likes to get attention both verbally and in action and is good at telling stories. RA is able to retell what the educator conveys. Aspects of motivation are given, namely by giving appreciation to students when they are enthusiastic about learning to write and read. YIH students who were initially less focused on paying attention to educators when delivering material, but now they are better at paying attention to educators while teaching after being motivated that studying in the room is a way of learning that makes YIH's spirit pay more attention when educators deliver material. PA students after being introduced to PA learning motivation became better at paying attention to educators while teaching, reading was quite good, but writing was not too neat. PA has also reduced teasing his friends to just chat, changes in PA are more striking in the desire to succeed in learning, namely by being given praise when PA is faced with a problem in learning difficulties but PA never gives up. Factors in the learning styles of students include health conditions, the relationship between students and educators or with their parents, as well as their own environment when studying at home which can affect students studying at school.